Determinants of Foreign Direct Investment in Germany - Abolghasemi, Seyed Mohammad Seyed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Foreign direct investment is defined as the investment made by a firm or an individual or an entity based in local country, into a firm, or entity based in another country (Dunning, 1977). This thesis aimed to analyze the determinants of FDI in one of the most powerful economics at the world; Germany. The period chosen for the study was January 1985 – December 2013. The variables chosen for this study were foreign direct investment, effective exchange rate, real GDP, interest rate, inflation, labor cost, import and export. To analyze the obtained data on each variable, various approaches were introduced. To investigate the determinants of FDI, gravity model was considered to be the most accurate and helpful approach (Egger, 2003). Hence the current study used the gravity model to implement the methodology. Two different equations were used to evaluate the financial and economical determinants of FDI separately. The first model described changes in FDI according to the changes in financial factor and the second model took the macroeconomic factors into consideration. The results of unit root tests revealed that the data was stationary at first level. After this test Vector Error Correction model and Johansen Co-integration tests were applied. Results on these analysis showed that variables chosen for study were insignificant in the short run and it could be said that they did not have any short run association to foreign direct investment. On the other hand, in the long run, all variables except inflation could not significantly affect the amount of FDI in Germany. Results showed that FDI in Germany was likely to be under the effect of changes in both economic and financial factors. However, economical factors tended to make more changes in FDI level in Germany. Keywords: Foreign direct investment (FDI), Vector Error Corection Model (VECM), Johansen co-integration, Germany. ………………………………………………………………………………………………………………………… ÖZ: Doğrudan yabancı yatırım, bir ülkedeki şirket, şahıs ya da kuruluşların başka bir ülkedeki bir şirkete ya da kuruluşa yatırım yapması olarak tanımlanır (Dunning,1977). Bu tezin amacı; dünyadaki önemli ülkelerden biri olan Almanyaiçin, doğrudan yabancı yatırımı belirleyen faktörleri analiz etmektir. Çalışmaiçin seçilen zaman periyodu January 1985 - December 2013 yıllarını arasındadır. Çalışmada kullanılan değişkenler; doğrudan yabancı yatırım, efektif döviz kuru, reel GSYİH, faiz oranları, enflasyon, işgücü maliyetleri, ithalat ve ihracattır. Her bir değişken için toplanan veriler ile ilgili çeşitli yaklaşımlar uygulanmıştır. Yerçekimi modelinin, doğrudan yabancı yatırım ile ilgili faktörlerin belirlenmesinde ki en doğru ve en yardımcı model olduğu varsayılmaktadır (Egger 2003). Bu nedenle, bu çalışmadaki methodolojinin uygulanmasında yerçekimi modeli kullanılmıştır. Doğrudan yabancı yatırımın finansal ve ekonomik belirleyicilerini değerlendirmek için iki farklı denklem kullanılmıştır. Bu modellerden birincisi finansal faktörlerin doğrudan yabancı yatırımlar üzerindeki etkisini incelerken ikinci model de makroekonomik faktörlerin doğrudan yabancı yatırımlar üzerindeki etkisi dikkate alınmıştır. Birim kök sınamasının sonuçları, çalışmada kullanılan verinin birinci derecede durağan olduğunu ortaya çıkarmıştır. Bu testin devamında yöney hata düzeltme ve Johansen eştümleşme modelleri uygulanmıştır. Bu analizlerden elde edilen bulgular, çalışmada kullanılan değişkenlerin kısa vade de anlamsız olduğunu ve doğrudan yabancı yatırımla kısa vadede bir ilişkilerinin olmadığını ortaya çıkarmıştır. Bunun yanında uzun vadede enflasyon dışındaki değişkenlerin Almanya‘daki yabancı doğrudan yatırımlarla anlamlı bir etkisi bulunamamıştır. Elde edilen sonuçlar, Almanya’da ki doğrudan yabancı yatırımların hem finansal hem de ekonomik faktörlerden etkilendiğini göstermektedir. Ancak ekonomik faktörler, Almanya’daki doğrudan yabancı yatırımları daha çok etkileme eğilimindedir. Anahtar Kelimeler: Doğrudan yabancı yatırım, Vektör hata Düzeltme modeli, Johansen Kointegrasyon, Almanya.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assist. Prof. Dr. Korhan Gökmenoğlu.
Keywords: Banking and Finance; Investments, Foreign - Germany; Foreign Direct Investment (FDI), Vector Error Correction Model (VECM), Johansen co-integration, Germany